# solve the system x-2y=0                            3x=0

givingiswinning | Student

x-2y=0

3x=0

x = 0

0 - 2y = 0

y = 0/-2 = 0

y=0

jess1999 | Student

x - 2y = 0

3x      = 0

First, multiply everything in the first equation by 3

By multiplying, your equation should look like

3x - 6y = 0

3x         = 0   now subtract 3x with 3x ( which means also subtract 0 with 0 and 6y with 0y )

By subtracting, your equation should look like

-6y = 0 now divide both sides by -6

By dividing your equation should look like

Now plug in 0 into one of the equation

3x - 6 ( 0 ) = 0 multiply -6 with 0

By multiplying, your equation should look like

3x - 0 = 0 divide both sides by 3

By dividing, your equation should look like

x = 0/3 simplify

atyourservice | Student

3x=0

x= 0/3

x=0

x-2y=0

0 - 2y =  0

-2y = 0

y = 0/-2

y=0

(0,0)

Wiggin42 | Student

x-2y=0      3x=0

if 3x = 0; then x = 0

0 - 2y = 0

y = 0/-2 = 0

Jyotsana | Student

3x=0

3x/3=0/3

x=0

0-2y=0

-2y=0

-2y/2=0/-2

y=0

giorgiana1976 | Student

Because the system is a homogeneous system, the only solution is zero solution.

It is obvious that the system could be solved using substitution method, too.

We'll note the equations of the system as if follows:

x-2y=0 (1)

3x=0    (2)

We'll divide by 3 in the equation (2) and we'll get:

x = 0

We'll substitute x by 0 in the first equation:

0 - 2y = 0

-2y = 0

We'll divide by -2 and we'll get:

y = 0

The solution of the system is {(0,0)}.

timothygrier | Student

7x+y=3

21x+5y=11

solve the system

william1941 | Student

I am not sure the question that you have provided is what you wanted to be solved and feel you have missed something. But based on the equations you have provided the system can be solved as follows:

You have provided 2 equations: x-2y=0 and 3x=0.

From 3x=0, we can infer that x=0.

Substituting x=0 in the equation x-2y=0 => 0-2y=0 or y=0.

Therefore the values of x and y that we get from the system of equations is x=0 and y=0.

neela | Student

To solve the system of equations:

x-2y = 0

3x= 0.

From the second equation, 3x= 0. So x = 0/3 = 0.

Substitute x = 0 in the 1st equation.

x-2y = 0,  0-2y = 0 . So  -2y = 0. So y = 0/-2 = 0

Therefore x= 0 and y = 0.